Botulinum Toxin A Therapy for Glabellar Lines Improves Emotional States: Evaluation of 47 Cases without Mental Disorders - Hiromi Hanayama; Jun Tada; Hiroto Terashi (Journal of Plastic and Reconstructive Surgery)
Objectives: Facial wrinkle treatment using botulinum toxin A (BT-A) is an extremely popular aesthetic procedure. Many studies have been conducted on the improvement of the mental states of depressive patients whose glabellar lines were treated with BT-A. It could be caused by afferent effects derived from the proprioception of related facial muscles, which is known as facial feedback hypothesis. This study highlights the impact of BT-A injections into the glabellar region on the emotional states of participants who have specifically no mental disorders. Methods: A total of 47 Asian participants (42 women and 5 men) without mental disorders completed the Japanese version of the Brief, Momentary Mood Checklist (BMC-J) before and 2 weeks after receiving the treatment for glabellar lines with BT- A injections. Results: Based on BMC-J scores reported by the participants, their emotional states statistically improved after treatment (P = 0.008), particularly in the concurrent decrease in negative emotions (P = 0.003). Conclusions: To our knowledge, this is the first study of the statistically significant effect of the BT-A treatment on the emotional state of subjects without mental disorders. The experiences of emotions derived from the motions of the frown muscles, which may be caused by the modulation of the amygdala activity, are not so complicated but extremely primitive, such as pleasure and unpleasure. This might be the reason why our results of BMC-J, which is used to measure basic emotions, indicated more clearly that negative emotions reduced compared with positive ones, in contrast to the finding of previous published reports that measured more complicated emotions such as feelings.